Development and Validation of the Interview of Personality Organization Processes in Adolescence (IPOP-A). Issue 3 (4th May 2021) - Fontana, Andrea; Ammaniti, Massimo; Callea, Antonino; Clarkin, Audrey; Clarkin, John F.; Kernberg, Otto F.
Abstract: The assessment of personality and personality pathology in adolescence represents a critical topic to understand adolescent's difficulties, predict long-term outcome in adulthood, and indicate adequate treatment. Personality Organization, and its underlying dimensions, plays an essential role in shaping how adolescents face their developmental tasks as they are connected with psychosocial functioning and psychopathological severity. However, few measures are available to assess personality organization during adolescence. The aim of the present research is to investigate the psychometric properties of the Interview of Personality Organization Processes in Adolescence (IPOP-A), a semi-structured interview designed for the assessment of the main personality organization dimensions in adolescence. Three studies were performed to explore the psychometric properties of the IPOP-A, in terms of factor structure, reliability, convergent, and discriminant validity. Exploratory and confirmatory factor analysis supported the IPOP-A construct validity. Furthermore, IPOP-A showed good reliability and evidenced a convergent and discriminant validity with DSM-oriented personality patterns, emotion dysregulation, identity disturbance, and psychopathology. Our results provide evidence of IPOP-A validity to assess emerging personality organization in adolescence. Furthermore, the IPOP-A is a promising tool to use in the clinical consultation and treatment planning for the adolescent.